Sp1, Instead of AhR, Regulates the Basal Transcription of Porcine CYP1A1 at the Proximal Promoter - Xie, Xuan; Jiang, Jun; Ye, Wenchu; Chen, Ruohong; Deng, Yiqun; Wen, Jikai (Frontiers in Pharmacology, 2018)
ABSTRACT Pigs are commonly used as an animal model to evaluate the toxic effects of exogenous compounds. Cytochrome P450 1A1 (CYP1A1) metabolizes numerous exogenous compounds and is abundantly expressed in the liver, kidneys and intestines. The high amino acid similarity between human and porcine CYP1A1 indicates that they probably have the same metabolic characteristics. Therefore, understanding the regulatory mechanism of CYP1A1 expression in pigs is particularly important for predicting the toxicology and metabolic kinetics of exogenous chemicals. Currently, the transcriptional regulation of porcine CYP1A1 has rarely been studied, especially regarding basal transcription. In this study, we first confirmed that the key regulatory elements of porcine CYP1A1 basal transactivation are in the proximal promoter region using promoter truncation analysis via a dual luciferase assay in a porcine kidney cell line LLC-PK1. Two overlapping cis elements, the xenobiotic response element (XRE) and GC box, in this proximal region potentially play key roles in the basal transactivation of porcine CYP1A1. Furthermore, using electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP), the GC box binding protein Sp1 was confirmed to bind to the proximal promoter of porcine CYP1A1, instead of AhR, the XRE binding protein. In LLC-PK1 cells, by knocking down either Sp1 or AhR, the expression of porcine CYP1A1 at the mRNA level and protein level was significantly downregulated, suggesting both proteins are important for porcine CYP1A1 expression. However, promoter activity analysis in LLC-PK1 cells treated with an AhR agonist and antagonist confirmed that AhR does not participate in the basal regulation of porcine CYP1A1 at the proximal promoter. In conclusion, our study revealed that the proximal promoter is the key regulatory region for porcine CYP1A1 basal expression. Although AhR plays an important role in the transactivation of porcine CYP1A1 expression, the key determinant transcription factor for its basal transactivation is Sp1 at the proximal promoter of porcine CYP1A1.